The association of magnetic resonance imaging features with five molecular subtypes of breast cancer - Van Thi Nguyen; Duc Huu Duong; Quang Thai Nguyen; Duy Thai Nguyen; Thi Linh Tran; Tra Giang Duong (European Journal of Radiology Open, 2024)
Objective: To identify the association of magnetic resonance imaging (MRI) features with molecular subtypes of breast cancer (BC). Materials and methods: A retrospective study was conducted on 112 invasive BC patients with preoperative breast MRI. The confirmed diagnosis and molecular subtypes of BC were based on the postoperative specimens. MRI features were collected by experienced radiologists. The association of MRI features of each subtype was compared to other molecular subtypes in univariate and multivariate logistic regression analyses. Results: The proportions of luminal A, luminal B HER2-negative, luminal B HER2-positive, HER2-enriched, and triple-negative BC were 14.3 %, 52.7 %, 12.5 %, 10.7 %, and 9.8 %, respectively. Luminal A was associated with hypo-isointensityon T2-weighted images (OR=6.214, 95 % CI: 1.163–33.215) and non-restricted diffusion on DWI-ADC (OR=6.694, 95 % CI: 1.172–38.235). Luminal B HER2-negative was related to the presence of mass (OR=7.245, 95 % CI: 1.760–29.889) and slow/medium initial enhancement pattern (OR=3.654, 95 % CI: 1.588–8.407). There were no associations between MRI features and luminal B HER2-positive. HER2-enriched tended to present as non-mass enhancement lesions (OR=20.498, 95 % CI: 3.145–133.584) with fast uptake in the initial postcontrast phase (OR=9.788, 95 % CI: 1.689–56.740), and distortion (OR=11.471, 95 % CI: 2.250–58.493). Triple-negative were associated with unifocal (OR=7.877, 95 % CI: 1.180–52.589), hyperintensityon T2-weighted images (OR=14.496, 95 % CI: 1.303–161.328), rim-enhanced lesions (OR=18.706, 95 % CI: 1.915–182.764), and surrounding tissue edema (OR=5.768, 95 % CI: 1.040–31.987). Conclusion: Each molecular subtype of BC has distinct features on breast MRI. These characteristics can serve as an adjunct to immunohistochemistry in diagnosing molecular subtypes, particularly in cases, where traditional methods yield equivocal results.